Feasibility study of a family- and school-based intervention for child behavior problems in Nepal - Ramesh P. Adhikari; Nawaraj Upadhaya; Emily N. Satinsky; Matthew D. Burkey; Brandon A. Kohrt; Mark J. D. Jordans (BMC, 2018)
Abstract Background This study evaluates the feasibility, acceptability, and outcomes of a combined school- and family-based intervention, delivered by psychosocial counselors, for children with behavior problems in rural Nepal. Methods Forty-one children participated at baseline. Two students moved to another district, meaning 39 children, ages 6-15, participated at both baseline and follow-up. Pre-post evaluation was used to assess behavioral changes over a 4-month follow-up period (n = 39). The primary outcome measure was the Disruptive Behavior International Scale-Nepal version (DBIS-N). The secondary outcome scales included the Child Functional Impairment Scale and the Eyberg Child Behavior Inventory (ECBI). Twelve key informant interviews were conducted with community stakeholders, including teachers, parents, and community members, to assess stakeholders' perceptions of the intervention. Results The study found that children's behavior problems as assessed on the DBIS-N were significantly lower at follow-up (M = 13.0, SD = 6.4) than at baseline (M = 20.5, SD = 3.8), p < 0.001, CI [5.57, 9.35]. Similarly, children's ECBI Intensity scores were significantly lower at follow-up (M = 9.9, SD = 8.5) than at baseline (M = 14.8, SD = 7.7), p < 0.005, 95% CI [1.76, 8.14]. The intervention also significantly improved children's daily functioning. Parents and teachers involved in the intervention found it acceptable and feasible for delivery to their children and students. Parents and teachers reported improved behaviors among children and the implementation of new behavior management techniques both at home and in the classroom. Conclusions Significant change in child outcome measures in this uncontrolled evaluation, alongside qualitative findings suggesting feasibility and acceptability, support moving toward a controlled trial to determine effectiveness.